Characterization of Sinus Disease in Patients with Yellow Nail Syndrome. Issue 2 (March 2020) - Gutierrez, Claudia N.; Low, Christopher M.; Stokken, Janalee K.; Choby, Garret; O'Brien, Erin K.
Objective: Yellow nail syndrome (YNS) is characterized by the triad of thickened yellow nails, primary lymphedema, and respiratory manifestations including bronchiectasis, chronic cough, pleural effusions, and sinusitis. The purpose of this study is to describe the manifestations of chronic rhinosinusitis (CRS) in patients with YNS and the comorbid manifestations. Methods: A retrospective review of patients with YNS with CRS from January 1, 1998 to January 1, 2018 was conducted. Their symptoms, comorbidities, and labs were reviewed. The patient's sinus computed tomography (CT) scans were then scored using the Lund–Mackay (LM) scoring system. Result: Thirty-six patients met the inclusion criteria. The average LM score was 10.2 ± 0.5 (mean ± SD). Sinus involvement included "frothy" dependent sinus secretions in 32 of 36 subjects. The most common location of sinus involvement was the maxillary sinuses (85%), then posterior ethmoid (81%), anterior ethmoid (76%), sphenoid (74%), and frontal sinuses (54%). Comorbid chronic cough (86%), bronchiectasis (65%), lymphedema (39%), and pleural effusion (19%) were also identified. Three patients (8%) had immunodeficiencies. Conclusion: This is the largest series describing the sinus manifestations of CRS in patients with YNS. Sinus CT scans showed frothy dependent secretions in the maxillary sinuses and posterior ethmoid sinuses most commonly. YNS patients with sinusitis more commonly presented with chronic cough or bronchiectasis than with pleural effusions or lymphedema. Otolaryngologists should consider the possibility of YNS in patients with CRS, chronic cough, yellow or thickened nail, and CT findings of frothy, dependent sinus secretions.